Efficacy and Safety of IL-5 Pathway-Targeting Biologics (Mepolizumab, Reslizumab, Benralizumab) in the Management of Hypereosinophilic Syndromes: A Systematic Review and Meta-Analysis - Yuniza; Melani; Ratna Maila Dewi Anggraini; Yenny Dian Andayani (HM Publisher, 2025)
Hypereosinophilic syndromes (HES) are rare disorders defined by persistent eosinophilia and eosinophil-driven organ damage. Interleukin-5 (IL-5) is the central cytokine governing eosinophil maturation and survival, establishing its pathway as a critical therapeutic target. While individual trials of biologics targeting the IL-5 pathway—mepolizumab, reslizumab, and benralizumab—have shown promise, a quantitative synthesis of their class-wide efficacy and safety in HES is needed. This study aimed to meta-analyze the evidence for these agents in managing HES. Following PRISMA guidelines, we systematically searched PubMed, Embase, and Cochrane Library through December 2024 for randomized controlled trials (RCTs) and prospective observational studies of IL-5 pathway biologics in patients with HES. Primary outcomes were the proportion of patients achieving hematologic response and the annualized rate of clinical exacerbations. Key secondary outcomes included oral corticosteroid (OCS) dose reduction and adverse events (AEs). Data were pooled using a random-effects model, with extensive, pre-planned subgroup and sensitivity analyses to explore heterogeneity. Seven studies (3 RCTs, 4 observational) involving 388 patients were included. Patients receiving IL-5 pathway biologics had significantly higher odds of achieving hematologic response (Odds Ratio [OR] 9.85; 95% Confidence Interval [CI] 5.12-18.96; p<0.0001), a finding robust to sensitivity analyses of different response definitions. The annualized exacerbation rate was reduced by 64% (Rate Ratio 0.36; 95% CI 0.25-0.52; p<0.0001). The intervention led to a mean daily OCS reduction of 12.5 mg (95% CI -15.8 to -9.2 mg; p<0.0001). Subgroup analysis revealed this effect was more pronounced in observational studies than in RCTs. The overall risk of AEs was not significantly increased. This meta-analysis provides robust evidence that biologics targeting the IL-5 pathway are highly effective and generally safe for managing PDGFRA-negative HES. They induce high rates of hematologic remission, substantially reduce clinical exacerbations, and facilitate a significant corticosteroid-sparing effect. These findings strongly support their role as a foundational component of modern HES therapy, though long-term safety and efficacy within distinct HES subtypes warrant further investigation.